Transformation of fiction from the Late Tang to Northern Song Dynasties - Ng, Yen Leng (2015)
This is a study of the different styles of literary narratives of the late Tang and Northern Song dynasties. These works include literary sketches and fictions in classical language and set on fantasy and romantic backgrounds, and short stories based on oral narratives in the “modern” language. The purpose is to examine the transformation of these works based on literary records, the concept of fictional writings, literary texts, and literary styles. Although the spirit of the Tang and Song dynasties differed, yet the literary transformation during this period is marked by a continuation of styles and internal structures. The discussion is placed in the context of the traditional view that holds the incipient fictions of the Tang in high regard at the expense of Song works. From the long-term and objective perspective, the trend towards the “modernization” of Tang fantasy writings that represent the incipient form of novels has a far-reaching influence on the study of the transformation of the literary forms of fiction. This literary transformation during the transitional period has to be viewed from the perspectives of prevalent social and political realities, regional cultures, changes in literary styles, and internal forms of the novels. By exploring the different strands of influence of the literary styles and attitudes on fictional writings, the study will attempt a re-appraisal of the historical significance of this literary genre.